MASKER GEL PEEL OFF DARI EKSTRAK WORTEL (Daucus carota L) - Selpia Sopianti Densi; Agustin Mila (Sekolah Tinggi Ilmu Kesehatan Borneo Lestari Banjarbaru, 2019)
ABSTRACTAntioxidant compounds from carrots come from non-enzymatic types, namely micronutrients in the form of vitamins. Some vitamins found in carrots function as antioxidants including vitamin C and beta carotene. The purpose of this study is to formulate carrot extract (Daucus carota L) into peel off gel preparations so that it is more practical in use and after drying the mask can be removed immediately to remove the remnants of dirt that stick to the surface of the facial skin without washing. The process of making preparations of peel off gel mask carrot extract (Daucus carota L) using maserasi method, the extract was carried out by eatingnol 96% solvent evaporation, using a variation of extract concentration 2.5%, 5%, 7.5%, the basis used as Gelling Agent was PVA and HPMC. The results showed that carrot extract (Daucus carota L) can be made as a peel off gel mask, affecting the physical properties of the peel off gel mask which includes the color of the preparation, pH of the preparation with the best formula F0, F1, F2 F3, dry time with the best formula F3 , F2, F1, F0, scattering power with the best formula F0, F1, F2, F3, adhesion with the best formula F3, F2, F1, F0.Keywords: Peel Off Gel Mask, Carrot, Physical Properties of Gel